Philosophy, Faith, and Water: Balinese Local Wisdom in Addressing Water Scarcity in Lombok - Susilo Edi Purwanto (International Journal Labs, 2026)
This study examines the role of Balinese local wisdom in Lombok in preserving water resources by emphasizing spiritual, cultural, and practical approaches that address water scarcity while promoting sustainable resource management. This research aims to analyze why and how Hindu belief-based local wisdom practices contribute to the preservation of springs amid increasingly complex environmental challenges. A qualitative approach was adopted, applying Talcott Parsons’ structural functional theory and Koentjaraningrat’s theory of religion as analytical frameworks. Data were collected through non-participant observation, semi-structured interviews with community members and religious leaders, and documentation conducted across Mataram City, West Lombok, and North Lombok. The findings indicate that Balinese Hindus perceive water as sacred and essential for sustaining life and prosperity. Belief systems embedded in rituals at Ulun Carik and Suranadi Temples cultivate ecological awareness and collective responsibility for protecting springs. Practical reliance on water resources also encourages careful utilization while maintaining sustainability for agricultural irrigation and food production. The study concludes that Balinese local wisdom in Lombok provides an effective model that integrates spiritual values with environmental stewardship. These findings offer valuable insights for policymakers, practitioners, and local communities seeking to integrate indigenous knowledge with modern technologies in addressing water scarcity and strengthening climate resilience in multicultural regions. The study further emphasizes that culturally embedded environmental ethics can complement formal conservation policies, encourage long-term community participation, reinforce sustainable water governance, preserve ecological balance, enhance adaptive capacity, support inclusive resource management, and inspire collaborative strategies for protecting springs against future environmental pressures and climate uncertainties.